A 3 dimensional numerical model to study the effect of GDL porosity on high temperature PEM fuel cells. (November 2020) - Jha, Vikalp; Hariharan, R.; Krishnamurthy, Balaji
Highlights: A model to study the effect of GDL porosity on high temperature fuel cells is studied. Simulation results indicate that a GDL porosity of 0.5–0.6 is optimum. Model results predict a 7% decrease in the oxygen consumption on the cathode when the GDL porosity is increased from 0.6 to 0.7 for the given set of parameters. The GDL porosity value is independent of inlet water vapor mass fraction, temperature and pressure. Abstract: A three dimensional mathematical model was developed to study the effect of GDL porosity on high temperature fuel cells. The effect of varying GDL porosity on the varying oxygen and water vapor concentration in the cathode flow fields was studied. Model predicts that a GDL porosity between the ranges of 0.5–0.6 was optimal for the performance of a high temperature fuel cell. For the given set of parameters, a 7% decrease in oxygen consumption on the cathode is seen when the GDL porosity is increased from 0.6 to 0.7. Further increasing the GDL porosity is seen to decrease the oxygen consumption further. Model predictions are compared with experimental data and found to compare well. Graphical abstract: Image, graphical abstract